Signal regulatory protein alpha (SIRPα) regulates the homeostasis of CD103+CD11b+ DCs in the intestinal lamina propria. Issue 12 (27th October 2014) - Scott, Charlotte L.; Zangerle Murray, Tamsin F. P.; Beckham, Katherine S. H.; Douce, Gillian; Mowat, Allan McI.
Abstract : Signal regulatory protein alpha (SIRPα/CD172a) is a conserved transmembrane protein thought to play an inhibitory role in immune function by binding the ubiquitous ligand CD47. SIRPα expression has been used to identify dendritic cell subsets across species and here we examined its expression and function on intestinal DCs in mice. Normal mucosa contains four subsets of DCs based on their expression of CD103 and CD11b and three of these express SIRPα. However, loss of SIRPα signaling in mice leads to a selective reduction in the CD103 + CD11b + subset of DCs in the small intestine, colon, and among migratory DCs in the mesenteric lymph node. In parallel, these mice have reduced numbers of TH 17 cells in steady‐state intestinal mucosa, and a defective TH 17 response to Citrobacter infection. Identical results were obtained in CD47KO mice. DC precursors from SIRPα mutant mice had an enhanced ability to generate CD103 + CD11b + DCs in vivo, but CD103 + CD11b + DCs from mutant mice were more prone to die by apoptosis. These data show a previously unappreciated and crucial role for SIRPα in the homeostasis of CD103 + CD11b + DCs in the intestine, as well as providing further evidence that this subset of DCs is critical for the development of mucosal TH 17 responses.